2021
DOI: 10.3389/feart.2021.617586
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Iodine-Mediated Stratospheric Ozone Loss Chemistry to Future Chemistry-Climate Scenarios

Abstract: As the chemical and physical state of the stratosphere evolves, so too will the rates of important ozone-destroying reactions. In this work, we evaluate the chemistry-climate sensitivity of reactions of stratospheric iodine, reporting the iodine alpha factor (the efficiency of ozone loss mediated by a single iodine atom relative to the ozone loss mediated by a single chlorine atom) and the iodine eta factor (the efficiency of ozone loss mediated by a single iodine atom relative to the ozone loss mediated by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Also, the further increase of sea surface temperature due to global warming, near-surface ozone, and sea surface iodide concentrations could be the reason for the intensification of iodine emissions in the future making the atmospheric amount of iodine to be vastly higher (Cuevas et al, 2018;Legrand et al, 2018;Cuevas et al, 2018;Koenig et al, 2020;Iglesias-Suarez et al, 2020;Carpenter et al, 2021). The effectiveness of iodine for ozone destruction is found to be stable in future warming scenarios and therefore its relative importance increases relative to the other halogens (Klobas et al, 2021).…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the further increase of sea surface temperature due to global warming, near-surface ozone, and sea surface iodide concentrations could be the reason for the intensification of iodine emissions in the future making the atmospheric amount of iodine to be vastly higher (Cuevas et al, 2018;Legrand et al, 2018;Cuevas et al, 2018;Koenig et al, 2020;Iglesias-Suarez et al, 2020;Carpenter et al, 2021). The effectiveness of iodine for ozone destruction is found to be stable in future warming scenarios and therefore its relative importance increases relative to the other halogens (Klobas et al, 2021).…”
Section: 4mentioning
confidence: 99%
“…While the future surface ozone evolution has a large spread in model projections over the 21 st century (Archibald et al, 2020) resulting in a large uncertainty in future iodine emissions, the continuous increase in surface temperatures is predicted to raise tropospheric iodine levels throughout the 21 st century based on Representative Concentration Pathway (RCP) scenarios (Iglesias-Suarez et al, 2020). Klobas et al (2021) showed that in future scenarios the effectiveness of iodine for ozone depletion is poorly sensitive to changes in the state of the stratosphere indicating an increase of relative importance of iodine over other halogens. Solomon et al (1994) presented one of the first studies demonstrating the potential role of iodine chemistry in stratospheric ozone loss using a two-dimensional model of atmospheric chemistry and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work suggested that iodine plays a more significant role than previously believed in stratospheric ozone chemistry and, moreover, that iodine is approximately 400-1000 times more effective at destroying ozone than stratospheric chlorine in the lower stratosphere. In the future, the share of halogen-induced ozone loss in the stratosphere due to reactions of iodine will likely be greater than it is today [7,8].…”
Section: Introductionmentioning
confidence: 95%
“…https://doi.org/10.1038/s41558-023-01671-y (~130 times larger than chlorine in the extra-polar stratosphere 35 ). The influence of anthropogenic VSL-Cl 27 and natural VSL-Br 36 on the total stratospheric ozone column has been previously described, although a comprehensive understanding of the chemical influence of VSLS on the LS ozone evolution has not been reached yet.…”
Section: Articlementioning
confidence: 99%